Marcadores específicos en el análisis de la artritis reumatoidea - Ruiz Gutierrez, Yusara Lisset (2017)
The present research study was based on the determination and prevention of Rheumatoid Arthritis (RA), which is a chronic inflammatory disease, autoimmune in nature, characterized by manifestations in the joints, is due to the intervention of genetic, environmental, ethnic, geographical and nutritional. In order to verify and verify the presence of this disease, some markers are used, such as rheumatoid factor. In our study, this marker was related to calcium by Fisher's test. An exact relation was not found for the small sample used, but with calcium decreased if an inverse relationship was found since 12.5% of people with RA who had decreased calcium levels were found and could become a prime factor in triggering the disease